PEMBERDAYAAN KELUARGA DALAM UPAYA PERCEPATAN PENURUNAN STUNTING PADA KELOMPOK KELUARGA BERISIKO STUNTING DI WILAYAH KERJA PUSKESMAS ASTAMBUL TAHUN 2024 - Noor Adha Aprilea; Norlaila Sofia; Nur Rohmah Prihatanti; Isnaniah, Isnaniah; Tut Barkinah; Norhalisa, Norhalisa; Pratiwi Sri Handayani; Ezliana, Ezliana (JURNAL PENGABDIAN MANDIRI, 2024)
The community service program titled "Empowering Families for Accelerated Reduction of Stunting in High-Risk Families in the Puskesmas Astambul Area for 2024" addresses the pressing issue of stunting, which significantly affects child growth and development. Conducted in the Puskesmas Astambul area, this initiative focuses on families at high risk of stunting, utilizing educational strategies and community engagement to improve nutritional practices and health awareness. The program involves implementing health education on family empowerment, the Healthy Living Movement (Germas), and the First 1000 Days of Life (HPK) initiative. The objectives are to increase families' knowledge about proper nutrition and health, promote practices for handwashing and sanitation, and foster community groups for sustained empowerment. Results show an increase in awareness regarding balanced nutrition and improved health practices among participants. Additionally, active participation in routine child monitoring and health practices was observed. This program aims to make a tangible impact on reducing stunting rates by addressing underlying risk factors and improving community health practices.